Small-Scale Farmers' Willingness to Pay for Information: A Comparison of Individual Purchase Decisions with Contributions to a Club Good - Michael Grimm; Nathalie Luck; Alia Bihrajihant Raya; Udit Sawhney (Institute of Labor Economics (IZA), 2024)
Soil tests provide information that can help farmers to reduce costs, increase yields and profits, and contribute to sustainable soil health, yet they are rarely used. In this study, we elicit small-scale farmers' willingness-to-pay (WTP) for rapid, low-cost soil tests using incentive-compatible auctions. Additionally, we test whether randomized participation in a sustainable soil management training can increase farmers' WTP. Furthermore, we elicit an alternative WTP by measuring the willingness to contribute to the costs of a soil test kit when farmer groups are offered kits containing 50 tests along with a training session that enables them to carry out the soil tests independently. Free riding is possible in this setting, and contributions will depend on social preferences and beliefs about the contributions of others. Our study shows that the WTP for soil information is considerable. Although we find some evidence for free riding, this does not significantly affect the WTP between the individual and the group auction. Our experiment demonstrates that integrating soil tests with existing extension services could be relatively straightforward. Subsidies can be justified by the potential environmental benefits.
Keywords: D71; H23; O13; O33; Q16; Q57; 330; technology adoption; soil tests; information constraints; willingness-to-pay; sustainability; public good games